2019
DOI: 10.1111/cid.12757
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year longitudinal cohort study on crown to implant ratio effect on marginal bone level in single implants

Abstract: Background A 5‐year longitudinal cohort study was carried out to evaluate the influence of anatomical crown to implant ratio (CIR) on peri‐implant marginal bone level (MBL) in single implants. Materials and Methods The longest possible implants, according to the availability of pristine bone, were inserted, one per patient, among periodontally healthy teeth in consecutively recruited subjects. CIR and MBL changes were measured on standardized radiographs. The relationship between MBL and multiple predictors wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Horizontal ridge augmentation has been illustrated using a variety of different techniques and materials [29]. In the case in question, we used a resorbable collagen membrane so as to avoid some of the drawbacks when using nonresorbable membranes, like the necessity for a second surgical procedure to remove the membrane combined with the risk of losing more of the regenerated bone due to flap reflection [30]. Moreover, the conclusion of an in vitro study which compared resorbable and nonresorbable membranes was that bioabsorbable membranes, particularly collagen and hyaluronic acid, may promote bone regeneration through their activity on osteoblasts which suggests that bioabsorbable membranes could be more apt than nonresorbable membranes because they encourage the regeneration and repair of bones [31].…”
Section: Resultsmentioning
confidence: 99%
“…Horizontal ridge augmentation has been illustrated using a variety of different techniques and materials [29]. In the case in question, we used a resorbable collagen membrane so as to avoid some of the drawbacks when using nonresorbable membranes, like the necessity for a second surgical procedure to remove the membrane combined with the risk of losing more of the regenerated bone due to flap reflection [30]. Moreover, the conclusion of an in vitro study which compared resorbable and nonresorbable membranes was that bioabsorbable membranes, particularly collagen and hyaluronic acid, may promote bone regeneration through their activity on osteoblasts which suggests that bioabsorbable membranes could be more apt than nonresorbable membranes because they encourage the regeneration and repair of bones [31].…”
Section: Resultsmentioning
confidence: 99%
“…It is also in line with the studies from Sutpideler et al [10] who found that the stresses were increased when the height of the prostheses increased, regardless of the angle of the applied force or the amount of offset. A study from Ramaglia et al [36] had already suggested that the marginal bone loss was neither influenced by the implants' length nor by the CIR.…”
Section: Discussionmentioning
confidence: 99%
“…Blanes [8], Okada et al [34] and Esfahrood et al [35] stated that the CIR does not influence the marginal bone maintenance. A longitudinal cohort study conducted by Ramaglia et al [36] suggested that bone loss is neither related to implant length nor to anatomical CIR. An in vitro experiment published by Nissan et al [37] reported that a different factor, the crown height space (CHS), would be more significant than CIR in assessing biomechanical-related detrimental effects, recommending vertical bone augmentation procedures when the CHS is 15 mm or longer [38].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies seem to only partially agree with this theory. A 5-year longitudinal cohort study published in 2019 [36] states that higher CIR values do not necessarily induce peri-implant bone loss and that using short implants may always be considered as an option in reduced bone heights. Other studies also state that increasing the CIR does not have significant effect on marginal bone loss [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%